2010
DOI: 10.7863/jum.2010.29.7.1041
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Diagnosis of Ovarian Tumors Using Pelvic Contrast-Enhanced Sonography

Abstract: Contrast-enhanced sonography improves preoperative diagnosis of ovarian tumors parameters. The significant parameters of the enhancement curve were significantly different for malignant and benign tumors. Borderline tumors contribute to a reduction of the discriminating capacity of the contrast agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 22 publications
1
16
0
1
Order By: Relevance
“…Although they reported that CE-TVS could not reliably distinguish borderline from malignant tumors, their conclusion was that CE-TVS can easily differentiate malignancies from other tumors. This result was also validated by Veyer who found signifi cant differences in enhancement curves in benign vs. malignant tumors [ 10 ].…”
Section: Clinical Studiessupporting
confidence: 64%
“…Although they reported that CE-TVS could not reliably distinguish borderline from malignant tumors, their conclusion was that CE-TVS can easily differentiate malignancies from other tumors. This result was also validated by Veyer who found signifi cant differences in enhancement curves in benign vs. malignant tumors [ 10 ].…”
Section: Clinical Studiessupporting
confidence: 64%
“…Specifically, wash-out time and area under curve (a reflection of total vascularity) were significantly different in benign vs. malignant ovarian tumors [3,4]. Other studies and a large multi-international one also found significant differences in CE-US of benign and early stage ovarian cancer [6][7][8].…”
Section: Transvaginal Microbubble Sonographymentioning
confidence: 72%
“…Several recent reports have shown that microbubble (contrast enhanced) Transvaginal Sonography is accurate in the early detection of ovarian cancer [3][4][5][6][7][8]. Significant differences in enhancement parameters have been documented in benign vs. malignant ovarian masses.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have investigated the use of contrast-enhanced sonography in the differential diagnosis of malignant versus benign ovarian masses. Diagnostic accuracy in these published studies varied widely, with the sensitivity ranging from 74% to 100% and the specificity ranging from 42% to 98% (D'Arcy et al 2004;Fleischer et al 2009;Huchon et al 2012;Kupesic and Kurjak 2000;Marret et al 2004;Orden et al 2003;Testa et al 2007Testa et al , 2009Veyer et al 2010;Xiang et al 2013), probably as a result of advances in technology, the heterogeneity of patient populations and so on. The overall accuracy of CEUS in the diagnosis of ovarian cancer has never been systematically assessed.…”
Section: Introductionmentioning
confidence: 96%
“…In the early stage, ovarian cancer is usually asymptomatic, and moreover, only a small number of the relatively common ovarian masses detected by imaging techniques are malignant, which makes it crucial to differentiate benign from malignant ovarian masses. Transvaginal sonography usually is the initial diagnostic modality of choice for assessment of most adnexal masses; however, some masses, especially early-stage ovarian cancer, remain difficult to classify by conventional transvaginal sonography, even in experienced hands (Veyer et al 2010;Wang et al 2011;Xiang et al 2013). Solid tumors and their metastases persist and grow through angiogenesis, which is characterized by a neovascular network with irregularly branching vessels derived from pre-existing normal venules that contain numerous arteriolar-venous malformations without an intact basement membrane (Feldmann et al 1999).…”
Section: Introductionmentioning
confidence: 99%